Differential type 1 interferon‐regulated gene expression in the brain during AIDS: interactions with viral diversity and neurovirulence. Issue 7 (22nd April 2013) - Polyak, Maria J.; Vivithanaporn, Pornpun; Maingat, Ferdinand G.; Walsh, John G.; Branton, William; Cohen, Eric A.; Meeker, Rick; Power, Christopher
Abstract : The lentiviruses, human and feline immunodeficiency viruses (HIV‐1 and FIV, respectively), infect the brain and cause neurovirulence, evident as neuronal injury, inflammation, and neurobehavioral abnormalities with diminished survival. Herein, different lentivirus infections in conjunction with neural cell viability were investigated, concentrating on type 1 interferon‐regulated pathways. Transcriptomic network analyses showed a preponderance of genes involved in type 1 interferon signaling, which was verified by increased expression of the type 1 interferon‐associated genes, Mx1 and CD317, in brains from HIV‐infected persons ( P <0.05). Leukocytes infected with different strains of FIV or HIV‐1 showed differential Mx1 and CD317 expression ( P <0.05). In vivo studies of animals infected with the FIV strains, FIVch or FIVncsu, revealed that FIVch ‐infected animals displayed deficits in memory and motor speed compared with the FIVncsu ‐ and mock‐infected groups ( P <0.05). TNF‐α, IL‐1β, and CD40 expression was increased in the brains of FIVch ‐infected animals; conversely, Mx1 and CD317 transcript levels were increased in the brains of FIVncsu ‐infected animals, principally in microglia ( P <0.05). Gliosis and neuronal loss were evident among FIVch ‐infected animals compared with mock‐ and FIVncsu ‐infected animals ( P <0.05). Lentiviral infections induce type 1 interferon‐regulated gene expression in microglia in a viral diversity‐dependent manner, representing a mechanism by which immune responses might be exploited to limit neurovirulence.—Polyak, M. J., Vivithanaporn, P., Maingat, F. G., Walsh, J. G., Branton, W., Cohen, E. A., Meeker, R., Power, C. Differential type 1 interferon‐regulated gene expression in the brain during AIDS: interactions with viral diversity and neurovirulence. FASEB J. 27, 2829‐2844 (2013). www.fasebj.org